STANDAR UKURAN PERUSAHAAN YANG TELAH MELAKUKAN MANAJEMEN PAJAK DENGAN INDIKATOR CASH ETR (Studi Empiris Pada Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia Periode 2013 – 2016) - Muji Handayani; Fadjar Harimurti; Djoko Kristianto (Universitas Slamet Riyadi, 2020)
Tax is an important source of funds that will be used to finance state expenditure. In tax collection there are differences in interests between tax authorities and companies. So that the company desire arises to minimize the tax burden that must be paid in order to increase profits. Efforts made by the company are to carry out tax management. The purpose of this study is to determine the standard size of the company that conducts tax management. This study uses empirical studies conducted on food and beverage companies listed on the Indonesia stock exchange for the period 2013 – 2016.The sampling technique uses purposive sampling method. The type of data used is qualitative data and quantitative data. The data analysis technique in this study uses statistical calculations (Range) to get the standard value of the size of the company that has done tax management. Based on the results of data analysis that has been done, it can be seen that companies that have carried out tax management are companies that have an ETR Cash value (CETR) of less than 0.23953.